PENDAMPINGAN K2 SABLON DALAM PENGEMBANGAN USAHA BIDANG JASA - Lutfia Nurul Hidayati; Novita Maulida Ikmal; Nur Holifah (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2022)
K2 Sablon is a business in the service sector which is currently being widely used in contemporary drink cups/containers. Today's drinks use a lot of cups that have a design/logo for branding the drink itself. This is very influential on the sale of some drinks. Very good and unique packaging is produced from a good logo or design. As recently happened, the demand for print and design made many owners overwhelmed with the request. We see the importance of raising this service product because we see his persistence in starting a business during the pandemic so that these service products have survived to this day. The problem experienced by Mr. Irwan Suryadi's business is that he is not yet proficient at making logos/designs according to customer requests. In addition, as an innovation, this business is not very developed because of the lack of good management and marketing or promotional tools. The solutions we offer are design training and coaching and online marketing. We hope that the K2 Screen Printing business can develop well in the midst of the current pandemic economic transition period and can support the economy of the community around the business location.